MIDDLE CEREBRAL ARTERY AND UMBLICAL ARTERY, PULSATILITY INDEX DOPPLER ASSOCIATIONS WITH PREGNANCY RISK (Proceedings of International Educators Conference, 2024)
Doppler velocimetry of the middle cerebral artery (MCA) is a method to assess impedance/resistance to flow in the fetal brain circulation. Vasodilatation of the MCA is considered to reflect a compensatory phenomenon often referred to as the “brain sparing effect”.